E-184 Transradial approach for pediatric diagnostic and neurointerventional surgery: single center case series and systematic review. (23rd July 2022) - Baig, A; Neumaier, J; Hashmi, Y; Monteiro, A; Waqas, M; Cappuzzo, J; Khawar, W; Snyder, K; Levy, E; Siddiqui, A; Reynolds, R; Davies, J
Abstract : Background: Recent widespread adoption of a transradial approach (TRA) in adults has encouraged its use and expansion in children; however, the safety and feasibility of the TRA in the latter has not been established. We evaluated these characteristics in our pediatric case series and compared our results with those in the literature. Methods: Our prospectively maintained database was retrospectively searched for consecutive patients ≤18 years of age who underwent diagnostic and interventional neuroangiography through the TRA. Patient demographics, indications for the procedure, use of ultrasound guidance, arterial size at the access site, intra- and post-procedure complications, and outcomes were recorded. For the literature review, systematic searches of PubMed, MEDLINE, and Embase databases were conducted using keywords with Boolean operators ('radial artery' AND 'pediatric') for studies published in English between January 2000 and September 2021. Continuous variables were reported as means or medians and respective standard deviations and interquartile ranges according to data normality. Categorical variables were reported as frequencies. Results: Twenty-one patients were included in our series (mean age, 16.6±2.23 years, range 9–17 years; male, 11[52.4%]). The TRA was used for diagnostic angiography in 15 cases (71.4%) and intervention in 6(28.6%). Ultrasound guidance and a 'radial cocktail' (verapamil-heparin-nitroglycerin) were used in all cases. Mean radial artery access-site diameter was 2.2±0.46mm. Two cases (9.5%) required conversion to femoral access. Two patients (9.5%) suffered reversible vasospasm. No radial artery occlusion or permanent neurologic deficits were recorded. Our systematic review showed similar results for vasospasm rates and procedural outcomes. Conclusions: Our results and the literature review demonstrate that the TRA is a safe and feasible option for pediatric patients. Routine use of ultrasound guidance, selection of appropriately sized catheters, and prophylactic use of vasodilators and antispasmodics can help ensure the success of the procedure and limit common access-site complications. Disclosures: A. Baig: None. J. Neumaier: None. Y. Hashmi: None. A. Monteiro: None. M. Waqas: None. J. Cappuzzo: None. W. Khawar: None. K. Snyder: 2; C; Canon Medical Systems Corporation, Penumbra Inc., Medtronic, and Jacobs Institute. 4; C; : Boston Scientific, Access Closure Inc, Niagara Gorge Medical. E. Levy: 2; C; Claret Medical, GLG Consulting, Guidepoint Global, Imperative Care, Medtronic, Rebound, StimMed;. 4; C; NeXtGen Biologics, RAPID Medical, Claret Medical, Cognition Medical, Imperative Care (formerly the Stroke Project), Rebound Therapeutics, StimMed, Three Rivers Medical;. A. Siddiqui: 2; C; Amnis Therapeutics, Boston Scientific, Canon Medical Systems USA Inc., Cerebrotech Medical Systems Inc., Cerenovus, Corindus Inc., Endostream Medical Ltd., Imperative Care, Inc. Integra LifeSciences C. 4; C; Adona Medical, Inc, Amnis Therapeutics, (Purchased by Boston Scientific October 2017), Blink TBI Inc., Buffalo Technology Partners Inc., Cerebrotech Medical Systems, Inc., Cognition Medical, Endostrea. R. Reynolds: None. J. Davies: 2; C; Medtronic. 4; C; Synchron, Cerebrotech, QAS.ai, RIST.